Study on the Novel The Mimic Men of Sir Vidiadhar Surajprasad Naipaul: Exploring the Impact of Colonialism on Identity in V.S. Naipaul's 'The Mimic Men' (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This study presents V.S Naipaul’s The Mimic Men as a post-colonial novel that depicts the effects of colonialism on colonized people. Through an autobiographical and confessional style, the narrator of the novel clarifies the influence of colonialism on his identity and how it impacts the social, political, and psychological aspects of the people of a small Caribbean island. The study attempts to highlight the manifestations related to the impact of colonization on self-identity and psychological confusion. It also handles the characters as men of mimicry and highlighted the reasons behind such an attitude.